Mineral trioxide aggregate in membrane form as a barrier membrane in guided bone regeneration - Min-Yong Lee; Hi-Won Yoon; Si-Yoon Lee; Kwang-Mahn Kim; Su-Jung Shin; Jae-Sung Kwon (Elsevier, 2024)
Background/purpose: In the field of conservative dentistry and endodontics, mineral trioxide aggregate (MTA), commonly used, possesses advantages such as biocompatibility, antimicrobial properties and osteogenic potential. This study investigated the feasibility of utilizing membrane form mineral trioxide aggregate (MTA) as a barrier membrane in guided bone regeneration (GBR) procedures. Materials and methods: Membranes were electrospun from three different formulations: 15 w/v% Polycaprolactone (PCL), 13 w/v% PCL + 2 w/v% MTA (2MTA), and 11 w/v% PCL + 4 w/v% MTA (4MTA). Physicochemical and mechanical properties of the electrospun membrane were compared, encompassing parameters such as surface morphology, fiber diameter distribution, chemical composition, phase identification, tensile stress, pH variation, and water contact angle. Moreover, the antimicrobial properties against of the electrospun membranes were assessed through direct exposure to streptococcus aureus (S. aureus) and candida albicans (C. albicans). Additionally, on the 7th day, biocompatibility and cell attachment were investigated with respect to L929 (fibroblast) and MC3T3 (pre-osteoblast) cells. Inhibition of L929 cell infiltration and the expression of osteogenic related genes including osteocalcin (OCN), alkaline phosphatase (ALP), and runt related transcription factor 2 (RUNX2) in MC3T3 cells on 7th and 14th days were also investigated. Results: PCL, 2MTA, and 4MTA exhibited no statistically differences in fiber diameter distribution and tensile stress. However, as the MTA content increased, wettability and pH also increased. Due to the elevated pH, 4MTA demonstrated the lowest viability S.aureus and C.albicans. All membranes were highly biocompatibility and promoted cell attachment, while effectively preventing L929 cell infiltration. Lastly 4MTA showed increase in OCN, ALP, and RUNX2 expression on both 7th and 14th day. Conclusion: The membrane form MTA possessed characteristics essential for a novel barrier membrane.